Acrylonitrile-styrene-acrylate (ASA) copolymer compositions with low uv absorber content and good uv resistance
By using UV absorber compositions with UV absorption capacity in the wavelength range of ≤380nm in the thermoplastic molding composition, replacing traditional UV absorbing agents, UV stability and environmental health problems are solved and UV stability is achieved Dual optimization and additive dosage.
Patent Information
- Application Number
- CN202380037197.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-29
- Filing Date
- 2023-04-26
- Publication Date
- 2024-12-20
AI Technical Summary
The amount of UV stabilizer used in the existing thermoplastic molding composition is relatively large, and traditional UV absorbers have a certain impact on the environment and health, so it is difficult to maintain the UV stability of the composition while reducing the total amount of additives.
The total amount of UV absorber is reduced by partially or completely replacing traditional benzotriazole UV absorber by using a UV absorber composition containing dyes, black pigments and white pigments with UV absorption capacity in the wavelength range of ≤380 nm, partially or completely replacing traditional benzotriazole UV absorber, reducing the total amount of UV absorber, by using a UV absorber composition containing dyes, black pigments and white pigments with UV absorption capacity in the wavelength range of ≤380 nm, , while maintaining the UV stability of the thermoplastic molding composition.
It is achieved while reducing the total amount of UV absorber, maintaining or improving the UV stability of the thermoplastic molding composition, reducing the potential risks to the environment and health without significantly affecting the mechanical properties of the composition.
Smart Images

Figure BDA0005107204840000173 
Figure BDA0005107204840000175 
Figure BDA0005107204840000177
Abstract
Description
Background Art
[0001] Impact modified molding compositions, such as acrylonitrile-styrene-acrylate (ASA), and their blends with other thermoplastic polymers are widely used in many applications, such as in the automotive industry, the electronics industry or for daily necessities. These thermoplastic polymer compositions are favored due to their good balance of impact strength, melt flow characteristics and high weathering stability.
[0002] In order to improve the weathering stability of ASA formulations for exterior applications, UV stabilizers such as hindered amine light stabilizers (HALS) compounds or UV absorbers are usually used. Some documents, such as US4692486, US9701813, EP-B 2593510 and DE-A10316198 teach the use of HALS stabilizers and their compositions as UV absorbers and light stabilizers. US2003 / 0074833, US7084197, US6800676, WO2007 / 113248 and DE10308506A disclose compositions of UV absorbers, HALS stabilizers and antioxidants.
[0003] However, from the perspective of economic and ecological sustainability, it is always desirable to reduce the total amount of additives in a polymer composition. This is especially true for potentially harmful additives. In view of these requirements, the inventors conducted experiments to reduce the total amount of UV stabilizers while substantially maintaining the UV stability of the ASA copolymer composition.
[0004] Surprisingly, it has been found that conventional UV absorbers, such as benzotriazole-type UV absorbers, can be replaced partly or completely by colorants with a UV absorption range of ≤ 380 nm without reducing the UV stability of the thermoplastic molding composition. Summary of the invention
[0005] The present invention relates to a thermoplastic molding composition P, comprising (or consisting of):
[0006] AB: Based on the molding composition P, 86-99.9% by weight, preferably 92.5-99.86% by weight, more preferably 95.5-99.83% by weight, typically 97-99.75% by weight of at least one graft copolymer composition as component AB, comprising:
[0007] A: Based on the weight of component AB, 30-80% by weight of at least one thermoplastic copolymer as component A, made from the following components:
[0008] A1: based on the copolymer A, 50-95% by weight of monomer A1, wherein monomer A1 is selected from styrene, α-methylstyrene, and a mixture of styrene and at least one other monomer selected from α-methylstyrene, p-methylstyrene and C1-C8 alkyl (meth) acrylate;
[0009] A2: 5-50% by weight of monomer A2, based on copolymer A, monomer A2 is selected from acrylonitrile and a mixture of acrylonitrile and at least one other monomer selected from methacrylonitrile, acrylamide, vinyl methyl ether, unsaturated carboxylic acid anhydride and unsaturated carboxylic acid imide;
[0010] B: Based on the weight of component AB, 20-70% by weight of at least one graft copolymer as component B, comprising:
[0011] B1: Based on the graft copolymer B, 50-90% by weight of at least one graft base B1 obtained by emulsion polymerization of:
[0012] B11: 70-99.9% by weight, based on the graft base B1, of at least one C1-C8 alkyl (meth)acrylate as monomer B11;
[0013] B12: 0.1-10% by weight of at least one multifunctional crosslinking monomer B12, based on the graft base B1;
[0014] B13: Based on the graft base B1, 0-29.5% by weight of at least one other copolymerizable monomer B13, preferably selected from styrene, α-methylstyrene, C1-C4 alkylstyrene, acrylonitrile, methacrylonitrile, methyl methacrylate, C9-C 20 Alkyl methacrylates and vinyl methyl ethers;
[0015] wherein the total of B11+B12+B13 provides 100% by weight of the at least one graft base B1; and
[0016] B2: Based on the graft copolymer B, 10-50% by weight of at least one graft shell B2, obtained by emulsion polymerization of the following components in the presence of the at least one graft base B1:
[0017] B21: 50-100% by weight of a monomer B21, based on the graft shell B2, selected from styrene, α-methylstyrene and a mixture of styrene and at least one other monomer selected from α-methylstyrene, p-methylstyrene and C1-C4 alkyl (meth) acrylates;
[0018] B22: 0-50% by weight of monomer B22, based on the graft shell B2, selected from acrylonitrile and a mixture of acrylonitrile with at least one other monomer selected from methacrylonitrile, acrylamide, vinyl methyl ether, unsaturated carboxylic acid anhydrides and unsaturated carboxylic acid imides;
[0019] B23: 0-20% by weight of at least one other copolymerizable monomer B23;
[0020] wherein the whole of B21+B22+B23 provides 100% by weight of the at least one graft shell B2;
[0021] wherein the graft base B1 and the graft shell B2 as a whole provide 100% by weight of the at least one graft copolymer B;
[0022] C: 0.1 to 4% by weight, preferably 0.13 to 3% by weight, more preferably 0.16 to 2.5% by weight, typically 0.2 to 2% by weight, based on the molding composition P, of at least one UV absorber as component C; and
[0023] D: 0-10% by weight, preferably 0.01-4.5% by weight, more preferably 0.01-2% by weight, usually 0.05-1% by weight of at least one other additive as component D, based on the molding composition P;
[0024] wherein the total amount of components A to D is 100% by weight of the molding composition P; wherein the UV absorber component C comprises at least one organic or inorganic component having UV absorption at least in a wavelength range of ≤380 nm; and wherein the UV absorber component C is at least partially selected from at least one black pigment, at least one white pigment and / or at least one dye having UV absorption at least in a wavelength range of ≤380 nm.
[0025] Within the meaning of the present invention, a dye is an organic or inorganic component which absorbs electromagnetic radiation at least in the visible wavelength range, i.e. in the wavelength range of 380 nm to 780 nm. Also, suitable dyes according to the present invention absorb electromagnetic radiation at least in the wavelength range of UV radiation, i.e. in the wavelength range below 380 nm, preferably in the range of 100 nm to 380 nm, more preferably in the range of 200 nm to 380 nm, in particular in the range of 250 nm to 380 nm.
[0026] In one embodiment of the present invention, the UV absorber component C preferably comprises (or consists of) at least one organic or inorganic component selected from at least one black pigment, a white pigment and / or at least one dye having UV absorption at least in a wavelength range of ≤380 nm. More preferably, the UV absorber component C comprises (or consists of) at least one dye having UV absorption at least in a wavelength range of ≤380 nm, preferably 100 nm-380 nm, more preferably 200 nm-380 nm, especially 250 nm-380 nm, at least one white pigment and / or at least one black pigment.
[0027] In another preferred embodiment, the UV absorber component C comprises (or consists of) at least one dye having UV absorption at least in a wavelength range of ≤380 nm, the dye being selected from red, orange and yellow dyes, especially yellow dyes. In addition, the UV absorber component C may comprise at least one non-pigment or dye organic component having UV absorption at least in a wavelength range of ≤380 nm, preferably 100 nm-380 nm, more preferably 200 nm-380 nm, especially 250 nm-380 nm, i.e., having no substantial absorption of electromagnetic radiation in the visible light range of 380 nm-780 nm. Known UV absorbers include compounds containing one or more benzotriazole moieties.
[0028] Preferably, the weight average particle size dw of the graft copolymer B is at least 50 nm, preferably at least 80 nm, more preferably at least 90 nm. This can be measured, for example, by means of an ultracentrifuge (Scholtan).
[0029] In a preferred embodiment of the present invention, the amount of the at least one graft copolymer composition AB, based on the thermoplastic molding composition P, is ≥ 98% by weight.
[0030] In a preferred embodiment, the at least one graft copolymer composition AB comprises:
[0031] A: based on the graft copolymer composition AB, 30-80% by weight of at least one thermoplastic copolymer selected from poly(styrene-acrylonitrile) (SAN), poly(α-methylstyrene / acrylonitrile) (AMSAN) and mixtures thereof as component A, and
[0032] B: Based on the graft copolymer composition AB, 20-70% by weight of at least one graft copolymer B, comprising:
[0033] B1: Based on the graft copolymer B, 50-90% by weight, preferably 55-90% by weight, more preferably 55-65% by weight of at least one graft base B1, obtained by emulsion polymerization of the following components:
[0034] B11: 70-99.9% by weight, preferably 87-99.5% by weight, of n-butyl acrylate as monomer B11, based on the graft base B1;
[0035] B12: 0.1-10% by weight, preferably 0.1-5% by weight, more preferably 1-2.5% by weight of at least one multifunctional crosslinking monomer B12, based on the graft base B1;
[0036] B13: Based on the graft base B1, 0-29.5% by weight, preferably 0-20% by weight, more preferably 0-10% by weight of at least one other copolymerizable monoethylenically unsaturated monomer B13, preferably selected from styrene, α-methylstyrene, C1-C4 alkylstyrene, acrylonitrile, methacrylonitrile, methyl methacrylate, C9-C 20 Alkyl methacrylates and vinyl methyl ethers;
[0037] wherein the sum of B11, B12 and B13 is equal to 100% by weight of B1; and
[0038] B2: 10-50% by weight, preferably 10-45% by weight, more preferably 35-45% by weight, based on the graft copolymer B, of at least one graft shell B2, which is obtained by emulsion polymerization of the following components in the presence of at least one graft base B1:
[0039] B21: 50-95% by weight, more preferably 65-80% by weight, most preferably 75-80% by weight, of styrene monomer B21, based on the graft shell B2;
[0040] B22: 5 to 50% by weight, more preferably 20 to 35% by weight, most preferably 20 to 25% by weight, based on the graft shell B2, of at least one monomer B22 selected from acrylonitrile and a mixture of acrylonitrile with at least one further monomer selected from methacrylonitrile;
[0041] B23: 0-20% by weight of at least one other copolymerizable monomer B23;
[0042] wherein the sum of B21, B22 and B23 is equal to 100% by weight of the at least one graft shell B2;
[0043] wherein the sum of the graft base B1 and the graft shell B2 is equal to 100% by weight of the graft copolymer B; and
[0044] The at least one graft copolymer B has a weight average particle size dw of 50-1000 nm, preferably 50-900 nm, and especially 80-700 nm.
[0045] A further object of the present invention is the use of the thermoplastic molding compositions P according to the invention for producing moldings.
[0046] In another aspect, the present invention also relates to a molded article comprising the thermoplastic molding composition P according to the invention.
[0047] According to the invention, the thermoplastic molding composition P comprises (or consists of):
[0048] AB: at least one graft copolymer composition AB, comprising at least one thermoplastic copolymer A and at least one graft copolymer B;
[0049] C: at least one UV absorber as component C, wherein the UV absorber component C is at least partially selected from at least one black pigment, at least one white pigment and / or at least one dye having UV absorption at least in the wavelength range of ≤380 nm; and
[0050] D: Optionally at least one further additive as component D.
[0051] According to one embodiment of the present invention, the thermoplastic molding composition P comprises (or consists of):
[0052] AB: at least one graft copolymer composition AB, comprising at least one thermoplastic copolymer A and at least one graft copolymer B;
[0053] C: at least one UV absorber as component C, wherein the UV absorber component C is at least partially selected from at least one black pigment, at least one white pigment and / or at least one dye having UV absorption at least in the wavelength range of ≤380 nm; and
[0054] D: at least one further additive as component D, wherein component D comprises at least one hindered amine light stabilizer (HALS).
[0055] Components A to D of the thermoplastic molding composition P are described in further detail below.
[0056] Graft copolymer component AB
[0057] The thermoplastic molding composition P according to the invention comprises, as component AB, 86 to 99.9% by weight, based on the molding composition P, of at least one graft copolymer composition.
[0058] The at least one graft copolymer composition AB comprises (or consists of) at least one thermoplastic copolymer as component A and at least one graft copolymer as component B, having the following composition:
[0059] A: Based on the graft copolymer composition AB, 30-80% by weight, preferably 40-75% by weight, more preferably 50-65% by weight, most preferably 55-65% by weight of at least one thermoplastic copolymer as component A, prepared from the following components:
[0060] A1: 50-95% by weight, preferably 55-80% by weight, more preferably 60-75% by weight, usually 62-68% by weight of monomer A1, based on copolymer A, selected from styrene, α-methylstyrene and a mixture of styrene and at least one other monomer selected from α-methylstyrene, p-methylstyrene and C1-C8 alkyl (meth) acrylate;
[0061] A2: 5-50% by weight, preferably 20-45% by weight, more preferably 25-40% by weight, usually 32-38% by weight of monomer A2, based on copolymer A, selected from acrylonitrile and a mixture of acrylonitrile and at least one other monomer selected from methacrylonitrile, acrylamide, vinyl methyl ether, unsaturated carboxylic acid anhydride and unsaturated carboxylic acid imide;
[0062] B: 20-70% by weight, preferably 25-60% by weight, more preferably 35-50% by weight, usually 35-45% by weight of at least one graft copolymer B, based on the graft copolymer composition AB, comprising:
[0063] B1: Based on the graft copolymer B, 50-90% by weight, preferably 52-80% by weight, more preferably 54-70% by weight, usually 55-65% by weight of at least one graft base B1, obtained by emulsion polymerization of the following components:
[0064] B11: 70-99.9% by weight, preferably 87-99.5% by weight, more preferably 87.5-99% by weight, based on the graft base B1, of at least one C1-C8 alkyl (meth)acrylate as monomer B11;
[0065] B12: 0.1-10% by weight, preferably 0.1-5% by weight, more preferably 1-2.5% by weight of at least one multifunctional crosslinking monomer B12, based on the graft base B1;
[0066] B13: Based on the graft base B1, 0-29.5% by weight, preferably 0-20% by weight, more preferably 0-10% by weight of at least one other copolymerizable monoethylenically unsaturated monomer B13, preferably selected from styrene, α-methylstyrene, C1-C4 alkylstyrene, acrylonitrile, methacrylonitrile, methyl methacrylate, C9-C 20 Alkyl methacrylates and vinyl methyl ethers;
[0067] wherein the total of B11+B12+B13 provides 100% by weight of at least one graft base B1; and
[0068] B2: 10-50% by weight, preferably 20-48% by weight, more preferably 30-46% by weight, typically 35-45% by weight of at least one graft shell B2, based on the graft copolymer B, obtained by emulsion polymerization of the following components in the presence of the at least one graft base B1:
[0069] B21: 50-100% by weight, preferably 60-90% by weight, more preferably 70-80% by weight, typically 73-77% by weight, based on the graft shell B2, of a monomer B21 selected from styrene, α-methylstyrene and a mixture of styrene with at least one further monomer selected from α-methylstyrene, p-methylstyrene and C1-C4 alkyl (meth) acrylates;
[0070] B22: 0-50% by weight, preferably 10-40% by weight, more preferably 20-30% by weight, typically 23-27% by weight, based on the graft shell B2, of a monomer B22 selected from acrylonitrile and a mixture of acrylonitrile with at least one other monomer selected from methacrylonitrile, acrylamide, vinyl methyl ether, unsaturated carboxylic acid anhydrides and unsaturated carboxylic acid imides;
[0071] B23: 0-20% by weight of at least one other comonomer B23;
[0072] wherein the whole of B21+B22+B23 provides 100% by weight of the at least one graft shell B2;
[0073] The graft base B1 and the graft shell B2 as a whole provide the at least one graft copolymer B in an amount of 100% by weight.
[0074] Thermoplastic Copolymer A
[0075] The thermoplastic copolymer A is preferably a rubber-free resin.
[0076] In a preferred embodiment of the present invention, monomer A1 is styrene or α-methylstyrene, and monomer A2 is acrylonitrile. In an alternative embodiment of the present invention, monomer A1 is a mixture of styrene and α-methylstyrene, and monomer A2 is acrylonitrile. Based on the total amount of monomer A1, the mixture preferably contains at least 10% by weight, preferably at least 50% by weight, and most preferably at least 90% by weight of styrene.
[0077] Particularly preferred thermoplastic copolymers A comprise (or consist of):
[0078] Based on the total copolymer A, 50-95% by weight, preferably 55-80% by weight, more preferably 60-75% by weight, typically 62-68% by weight of monomer A1 is selected from styrene, α-methylstyrene or a mixture of styrene and α-methylstyrene, and
[0079] Based on the total copolymer A, 5-50% by weight, preferably 20-45% by weight, more preferably 25-40% by weight, usually 32-38% by weight of monomer A2 is selected from acrylonitrile or a mixture of acrylonitrile and methacrylonitrile.
[0080] Most preferably, the thermoplastic copolymer A contains 35 weight percent acrylonitrile or less, based on the total copolymer A.
[0081] The weight average molecular weight M of copolymer A W The viscosity number VN of the copolymer A is preferably 50-100 cm 3 / g, more preferably 55-85g / cm 3 (Measured according to DIN 53726 at 25° C., the weight percentage of dimethylformamide is 0.5%).
[0082] Poly(styrene-acrylonitrile) (SAN) and poly(α-methylstyrene / acrylonitrile) (AMSAN) are known and their preparation, for example by free-radical polymerization, in particular by emulsion, suspension, solution and bulk polymerization, is well documented in the literature.
[0083] The synthesis of thermoplastic copolymers A is described, for example, in DE-A 2420358 and DE-A 2724360. Suitable thermoplastic copolymers are also described in DE-A 19713509. The synthesis of thermoplastic copolymers A can be initiated thermally or by adding initiators, especially free radical initiators, such as peroxides. Suitable thermoplastic copolymers A are preferably prepared by bulk polymerization or solution polymerization. The copolymers can be added individually or as any mixture.
[0084] Graft copolymer B
[0085] According to the invention, the graft copolymer composition AB comprises at least one graft copolymer B, in particular an ASA graft rubber, based on the graft copolymer B, 50-90% by weight, preferably 55-90% by weight, of at least one graft base B1 and 10-50% by weight, preferably 10-45% by weight, of at least one graft shell B2, preferably one to three graft shells B2, wherein the total amount of graft base B1 and graft shell B2 is equal to 100% by weight.
[0086] In a preferred embodiment of the present invention, the graft copolymer B comprises 10-50% by weight, preferably 10-45% by weight, most preferably 35-45% by weight of at least one graft shell B2, based on the total graft copolymer B, which is obtained by emulsion polymerization of the following components:
[0087] B21: 50-95% by weight, preferably 65-80% by weight, typically 75-80% by weight, based on the graft shell B2, of at least one monomer B21 selected from styrene, α-methylstyrene or a mixture of styrene with at least one other monomer selected from α-methylstyrene, p-methylstyrene, C1-C4 alkyl(meth)acrylates (e.g. methyl methacrylate, ethyl methacrylate), preferably selected from styrene, α-methylstyrene or a mixture of styrene with α-methylstyrene or methyl methacrylate; and
[0088] B22: 5 to 50% by weight, preferably 20 to 35% by weight, typically 20 to 25% by weight, based on the graft shell B2, of at least one monomer B22 selected from acrylonitrile or a mixture of acrylonitrile with at least one further monomer selected from methacrylonitrile, acrylamide, vinyl methyl ether, unsaturated carboxylic acid anhydrides (e.g. maleic anhydride, phthalic anhydride) and unsaturated carboxylic acid imides (e.g. N-substituted maleimides, such as N-cyclohexylmaleimide and N-phenylmaleimide), preferably selected from acrylonitrile or a mixture of acrylonitrile with methacrylonitrile;
[0089] The total amount of B21 and B22 is equal to 100% by weight of the graft copolymer B.
[0090] Preferred graft copolymers B comprise a graft base B1 of a crosslinked polybutyl acrylate rubber as described above and only one graft shell B2, which is obtained by emulsion polymerization from monomers B21 and B22, as described above, in the presence of the graft base B1 (single graft shell B2), in particular styrene or acrylonitrile. Further preferred graft copolymers B comprise a graft base B1 (as described above), comprising a crosslinked polybutyl acrylate rubber and two graft shells B2' and B2", wherein B2' is obtained by emulsion polymerization from monomers B21, in particular styrene, in the presence of the graft base B1. The graft shell B2" is obtained by further emulsion polymerization of monomers B21 and B22 (as described above), in particular styrene and acrylonitrile, in the presence of the graft base B1 after B2' has been grafted (two-stage grafting).
[0091] It is particularly preferred that the graft base B1 is obtained by emulsion polymerization of the following components:
[0092] B11: preferably 87-99.5% by weight of at least one C4-C8 alkyl (meth) acrylate, preferably n-butyl acrylate and / or 2-ethylhexyl acrylate, most preferably only n-butyl acrylate, based on the graft base B1;
[0093] B12: 0.5-5% by weight, preferably 0.5-3% by weight, preferably 1-2.5% by weight, based on the graft base B1, of at least one multifunctional crosslinking monomer B12, preferably selected from isoprene, butadiene, chloroprene, alkylene glycol di(meth)acrylate, allyl(meth)acrylate, divinylbenzene, diallyl maleate, diallyl fumarate, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate and dicyclopentadienyl acrylate (DCPA), particularly preferably allyl(meth)acrylate and / or dicyclopentadienyl acrylate (DCPA);
[0094] B13: Based on the graft base B1, 0-29.9% by weight, preferably 0-10% by weight, preferably 0.5-10% by weight of at least one other copolymerizable monoethylenically unsaturated monomer B13, preferably selected from styrene, α-methylstyrene, C1-C4 alkylstyrene, acrylonitrile, methacrylonitrile, methyl methacrylate, C9-C 20 Alkyl methacrylates and vinyl methyl ethers;
[0095] The total amount of B11, B12 and B13 is equal to 100% by weight.
[0096] Preferred monomers B11 for preparing the graft base B1 are alkyl acrylates and / or alkyl methacrylates, in which the alkyl group has 1 to 8, preferably 4 to 8, carbon atoms. Particularly preferred are n-butyl acrylate and / or 2-ethylhexyl acrylate, most preferred is n-butyl acrylate as monomer B11. Preferably, the alkyl acrylates are used alone as monomer B11.
[0097] In order to crosslink the C1-C8 alkyl (meth) acrylate monomer B11 and thus the graft base B1, the monomer B11 is polymerized in the presence of 0.1-10% by weight, preferably 0.1-5% by weight, preferably 0.5-3% by weight, preferably 1-4% by weight, more preferably 1-2.5% by weight of a multifunctional crosslinking monomer B12, based on the graft base B1. Suitable monomers B12 are in particular multifunctional crosslinking monomers, which can be copolymerized with the monomers, in particular B11 and B13. Suitable multifunctional crosslinking monomers B12 contain two or more, preferably two or three, more preferably only two ethylene double bonds, which are preferably not 1,3 conjugated. Examples of suitable multifunctional crosslinking monomers B12 are allyl (meth) acrylate, divinylbenzene, carboxylic acid diallyl esters, such as maleic acid diallyl ester, fumaric acid diallyl ester and phthalic acid diallyl ester.
[0098] As described in DE-A 1260135, the acrylic ester of tricyclodecanol (dicyclopentadienyl acrylate, DCPA) is also a preferred polyfunctional crosslinking monomer B12.
[0099] The multifunctional cross-linking monomer B12 is especially at least one selected from the following list: allyl (meth)acrylate, divinylbenzene, diallyl maleate, diallyl fumarate, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate and dicyclopentadienyl acrylate (DCPA), preferably selected from allyl (meth)acrylate, divinylbenzene, diallyl maleate, diallyl fumarate, diallyl phthalate and dicyclopentadienyl acrylate (DCPA), and particularly preferably selected from allyl (meth)acrylate and dicyclopentadienyl acrylate (DCPA).
[0100] In a preferred embodiment, 1-2.5% by weight, preferably 1.5-2.1% by weight, based on the graft base B1, of dicyclopentadienyl acrylate (DCPA) is used alone as monomer B12 or mixed with another of the above monomers B12, in particular with allyl (meth)acrylate.
[0101] Furthermore, the graft base B1 may optionally comprise one or more copolymerizable monoethylenically unsaturated monomers B13 which are different from B11 and B12. Monomer B13 may be selected, for example, from styrene, acrylonitrile, methyl methacrylate and vinyl methyl ether.
[0102] In a preferred embodiment, at least one graft base B1 is obtained by emulsion polymerization of the following components:
[0103] B11: 90-99.9% by weight, preferably 97-99.5% by weight, based on the graft base B1, of at least one C1-C8 alkyl (meth) acrylate, preferably n-butyl acrylate;
[0104] B12: 0.1-10% by weight, preferably 0.5-3% by weight, most preferably 1-2.5% by weight, based on the graft base B1, of at least one multifunctional crosslinking monomer B12; selected from isoprene, butadiene, chloroprene, alkylene glycol di(meth)acrylate, allyl(meth)acrylate, divinylbenzene, diallyl maleate, diallyl fumarate, diallyl phthalate and dicyclopentadienyl acrylate (DCPA), particularly preferably allyl(meth)acrylate and / or dicyclopentadienyl acrylate (DCPA);
[0105] The sum of B11 and B12 is equal to 100% by weight of B1.
[0106] Graft bases B1 comprising monomers B11, B12 and optionally B13 and their preparation are known and described in the literature, for example in DE-A 2826925, DE-A 3149358 and DE-A 3414118.
[0107] Like the emulsion polymerization for synthesizing the graft base B1, the graft polymerization for synthesizing the graft shell B2 (e.g. B2' and B2") is usually carried out in the same container. During the reaction, additives such as emulsifiers, pH buffers and initiators can be added. The monomers of the graft shell, especially the monomers B21 and B22, can be added to the reaction mixture all at once or gradually in several steps, preferably continuously during the polymerization. When the monomers B21 and / or B22 are added in several steps, a multilayer graft shell B2 is usually obtained.
[0108] Suitable emulsifiers, buffers and initiators are described in WO 2015 / 150223 and WO 2015 / 078751.
[0109] In a preferred embodiment, the graft copolymer B (having only one graft layer B2) comprises:
[0110] B1: 50-70% by weight, preferably 55-65% by weight, typically 58-65% by weight of at least one graft base (as described above), based on the graft copolymer B;
[0111] B2: 30-50% by weight, preferably 35-45% by weight, typically 35-42% by weight, based on the graft copolymer B, of at least one graft shell B2, obtained by emulsion polymerization of the following components in the presence of at least one graft base B1:
[0112] B21: based on the graft base B2, 50-95% by weight, preferably 65-80% by weight, more preferably 75-80% by weight of monomer B21, selected from styrene, α-methylstyrene or a mixture of styrene and at least one other monomer selected from α-methylstyrene, p-methylstyrene and C1-C4 alkyl (meth) acrylate (for example methyl methacrylate, ethyl methacrylate), preferably selected from styrene, α-methylstyrene or a mixture of styrene and α-methylstyrene or methyl methacrylate; and
[0113] B22: 5 to 50% by weight, preferably 20 to 35% by weight, typically 20 to 25% by weight, of a monomer B22, based on the graft shell B2, selected from acrylonitrile or a mixture of acrylonitrile with at least one further monomer selected from methacrylonitrile, acrylamide, vinyl methyl ether, an unsaturated carboxylic acid anhydride (e.g. maleic anhydride, phthalic anhydride) and an unsaturated carboxylic acid imide (e.g. N-substituted maleimide, such as N-cyclohexylmaleimide and N-phenylmaleimide); preferably selected from acrylonitrile or a mixture of acrylonitrile with methacrylonitrile;
[0114] The total amount of the graft base B1 and the graft shell B2 is equal to 100% by weight of the graft copolymer B.
[0115] In a preferred embodiment of the present invention, the graft copolymer B (including two graft shells B2' and B2") comprises
[0116] B1: based on the graft copolymer B, 50-70% by weight, preferably 60-70% by weight of at least one graft base B1, as described above;
[0117] B2': 10-30% by weight, preferably 10-20% by weight, usually 10-15% by weight, based on the graft copolymer B, of at least one graft shell B2', obtained by emulsion polymerization of the following components in the presence of the graft base B1:
[0118] B21': 100% by weight of monomer B21', based on the graft shell B2', selected from styrene, α-methylstyrene or a mixture of styrene and at least one other monomer selected from α-methylstyrene, p-methylstyrene and C1-C4 alkyl (meth) acrylates (e.g. methyl methacrylate, ethyl methacrylate); and
[0119] B2″: Based on the graft copolymer B, 20-40% by weight, preferably 20-30% by weight, usually 25-30% by weight of at least one graft shell B2″, in the presence of graft base B1 and graft shell B2′, obtained by emulsion polymerization of the following components:
[0120] B21″: 50-95% by weight, preferably 65-80% by weight, typically 70-80% by weight, based on the graft shell B2″, of a monomer B21″ selected from styrene, α-methylstyrene or a mixture of styrene with at least one other monomer selected from α-methylstyrene, p-methylstyrene and C1-C4 alkyl (meth)acrylates (e.g. methyl methacrylate, ethyl methacrylate), preferably selected from styrene, α-methylstyrene or a mixture of styrene with α-methylstyrene or methyl methacrylate; and
[0121] B22″: 5-50% by weight, preferably 20-35% by weight, more preferably 20-30% by weight, based on the graft shell B2″, of at least one monomer B22″ selected from acrylonitrile or a mixture of acrylonitrile and at least one other monomer selected from methacrylonitrile, acrylamide, vinyl methyl ether, unsaturated carboxylic acid anhydrides (e.g. maleic anhydride, phthalic anhydride) and unsaturated carboxylic acid imides (e.g. N-substituted maleimides, such as N-cyclohexylmaleimide and N-phenylmaleimide).
[0122] Preferably, monomers B21, B21′ and B21″ are styrene or a mixture of styrene and α-methylstyrene.
[0123] Preferably, monomers B22 and B22″ are acrylonitrile or a mixture of acrylonitrile with at least one other monomer selected from methacrylonitrile, maleic anhydride, N-cyclohexylmaleimide, N-phenylmaleimide, more preferably a mixture of acrylonitrile or acrylonitrile with at least one other monomer selected from methacrylonitrile and maleic anhydride.
[0124] Monomers B23 and B23″ may be selected from copolymerizable ethylenically unsaturated monomers (e.g. C1-C8 alkyl methacrylate, C9-C 20The present invention relates to a polyfunctional crosslinking monomer, wherein the polyfunctional crosslinking monomer is selected from the group consisting of isoprene, butadiene, chloroprene, alkylene glycol di(meth)acrylate, allyl (meth)acrylate, divinylbenzene, diallyl maleate, diallyl fumarate, diallyl phthalate and dicyclopentadienyl acrylate (DCPA).
[0125] In a more preferred embodiment of the present invention, monomers B21, B21' and B21" are styrene and monomers B22 and B22'" are acrylonitrile.
[0126] The graft copolymer B (obtained in latex form) generally has a weight average particle size dw of 50-1000 nm, preferably 90-700 nm. The particle size of the latex particles can be controlled during the synthesis by suitable methods known from, for example, DE-A 2826925.
[0127] Typically, the average particle diameter can be measured by ultracentrifugation (as described in W. Scholtan, H. Lange, Kolloid-ZuZ Polymere 250 (1972), pages 782-796) or using hydrodynamic chromatography HDC (as described in W. Wohlleben, H. Schuch, "Measurement of Particle Size Distribution of Polymer Latexes", 2010, editor: L. Gugliotta, J. Vega, pages 130-153). 50 Represents the value of the particle size distribution curve, where 50% of the particles (e.g. polyacrylate latex) have a smaller diameter, with d 50 The other 50% have a larger diameter than the value. In a similar manner, for example, d 90 The value gives the particle size where 90% of the particles have a smaller diameter. The average particle size (mass average, d w ) can also be determined by turbidity measurement as described in Lange, Kolloid-Zeitschrift und Zeitschrift Polymere, Vol. 223, p. 1.
[0128] In one embodiment of the present invention, the graft copolymer B has a unimodal weight average particle size distribution dw.
[0129] However, in another embodiment of the present invention, the graft copolymer B can have a multimodal weight average particle size distribution dw, more preferably a bimodal weight average particle size distribution dw, that is, it exists in the form of a mixture of at least two different graft copolymers BI and B-II, wherein the weight average particle sizes dw of the graft copolymers BI and B-II are different.
[0130] The graft copolymer B comprises in particular at least one of the graft copolymers BI and B-II, wherein:
[0131] The weight average particle size dw of the graft copolymer BI is 50-180 nm, preferably 80-150 nm, usually 90-100 nm (small size ASA rubber); and
[0132] The weight average particle size dw of the graft copolymer B-II is 200-800 nm, preferably 300-700 nm, usually 400-600 nm (large size ASA rubber).
[0133] Suitable large-scale crosslinked C1-C8 alkyl (meth)acrylate polymer graft bases B1-II can be prepared by known methods for producing large-scale dispersions, usually by seed polymerization, as described in DE 1911882 for producing ASA polymers.
[0134] According to the method, the average particle size dw of the small-sized cross-linked acrylate emulsion (seed latex) obtained by emulsion polymerization of C1-C8 alkyl (meth) acrylate, cross-linking monomer and optional comonomer, emulsifier and possible buffer is 50-180nm, preferably less than 120nm, which is further polymerized. The reaction conditions (Journal of Applied Polymer Science, Vol. 9 (1965), pp. 2929-2938) are adjusted to allow only the existing (seed) latex particles to grow further without forming new latex particles. An initiator is usually used. The particle size of the obtained graft copolymer B-II (large-sized rubber) can be adjusted by changing the weight ratio of seed latex to monomer.
[0135] The graft copolymer B-II is preferably obtained by emulsion polymerization of styrene or α-methylstyrene and acrylonitrile in the presence of a previously prepared large-scale graft base B1-II.
[0136] In order to prepare the thermoplastic resin of the present invention, graft copolymer BI and B-II can be combined, especially in step d (component mixing). The weight ratio of graft copolymer BI and B-II can be varied within a wide range. Preferably, the graft copolymer is a mixture of graft copolymer BI and B-II, wherein the weight ratio of graft copolymer BI to graft copolymer B-II is 90:10-10:90, preferably 80:20-20:80, and most preferably 70:30-35:65.
[0137] Preferably, the graft copolymers BI and B-II are prepared and separated separately. Alternatively, the graft copolymers BI and B-II can be prepared and separated separately and then mixed together.
[0138] Graft copolymers of different particle sizes can also be obtained by known agglomeration processes, with bimodal particle size distributions, in particular 50-180 nm and 200-800 nm. For example, DE-A 3615607 describes graft copolymers having large and small particle sizes.
[0139] In a preferred embodiment of the present invention, the graft copolymer B has a weight average particle size dw of at least 100 nm. The inventors have found that the graft copolymer B having a weight average particle size dw of at least 100 nm exhibits improved mechanical properties after artificial weathering conditions. Graft copolymers B having a weight average particle size dw of at least 300 nm, more preferably at least 350 nm, achieve better performance.
[0140] Furthermore, it is also possible to use graft copolymers B which have two or more different graft shells B2. For example, EP-A 0111260 and WO 2015 / 078751 describe graft copolymers having a multilayer graft shell.
[0141] The monomers B21 and B22 used for the emulsion polymerization of the graft copolymer B are preferably a mixture of styrene and acrylonitrile in a mass ratio of 95:5 to 50:50, usually 80:20 to 65:35.
[0142] Furthermore, molecular weight regulators can be used for the preparation of the graft base B1 and / or for the emulsion polymerization of at least one graft copolymer B, preferably in an amount of 0.01 to 2% by weight, typically 0.05 to 1% by weight (relative to the total amount of monomers used for the emulsion polymerization). Suitable molecular weight regulators are, for example, alkyl mercaptans, such as n-dodecyl mercaptan, tert-dodecyl mercaptan; dimers α-methylstyrene and terpinolene.
[0143] Suitable initiators for preparing the graft base B1 and / or for the emulsion polymerization of at least one graft copolymer B are any initiators. Preference is given to using at least one organic and / or inorganic peroxide compound (containing at least one peroxide group ROOH and / or ROOR) as initiator. In particular, inorganic peroxide salts such as aluminum, sodium or potassium persulfates, perphosphates or perborates can be used. Most preferred are sodium persulfate and potassium persulfate.
[0144] In a preferred embodiment of the present invention, an inorganic peroxide salt, preferably an inorganic persulfate, preferably sodium persulfate and / or potassium persulfate is used for the emulsion polymerization of the graft copolymer B.
[0145] Typical anionic emulsifiers can be used as emulsifiers for preparing the graft base B1 and / or for the emulsion polymerization of at least one graft copolymer B. Preferred emulsifiers are, for example, alkyl sulfates, alkyl sulfonates, aryl alkyl sulfonates, saturated or unsaturated fatty acid soaps and alkaline disproportionated or hydrated abietic acid or tall oil acid or mixtures thereof. Preference is given to using emulsifiers containing carboxyl groups (e.g. C 10 -C 18 Fatty acid salts, disproportionated abietic acid or tall oil acid, emulsifiers according to DE-OS 3639904 and DE-OS 3913509).
[0146] Typically, a suitable buffer is used for the preparation of the graft copolymer B, such as sodium carbonate or sodium bicarbonate. Suitable emulsifiers, buffers and initiators are also mentioned in WO 2015 / 150223 and WO 2015 / 078751.
[0147] The temperature during the emulsion polymerization of the graft copolymer B is generally 25-160° C., preferably 40-90° C. Suitable emulsifiers are as described above. Typical temperature management can be applied during the reaction, such as an isothermal process, and the polymerization is preferably carried out in a manner that the temperature difference between the start and the end of the reaction is kept less than 20° C., preferably less than 15° C., and most preferably less than 5° C.
[0148] According to the present invention, the preparation of the graft copolymer B, in particular the preparation of the graft copolymers BI and B-II, is carried out by emulsion polymerization. Common implementations of emulsion polymerization in batch or continuous mode are well known to those skilled in the art.
[0149] The monomers B2 of the graft shell, ie the monomers B21 and B22, are added successively to the graft base B2 in suitable amounts and weight ratios, in particular individually or as a monomer mixture. These monomers are usually added to the graft base B1 in a manner known to the person skilled in the art.
[0150] UV absorber (component C)
[0151] The thermoplastic molding compositions P according to the invention comprise, as component C, from 0.1 to 4%, based on the molding composition P, of at least one UV absorber.
[0152] The UV absorber component C comprises at least one organic or inorganic component having UV absorption at least in the wavelength range of ≤380 nm, in particular in the wavelength range of 200-380 nm.
[0153] Known UV absorbers that meet the UV absorption requirements are not dyes within the meaning of the present invention, i.e., are colorless and do not substantially absorb electromagnetic radiation in the visible wavelength range of 380 nm to 780 nm. Such UV absorbers include 2-(2-hydroxyphenyl)-2H-benzotriazoles, such as the known commercial hydroxyphenyl-2H-benzotriazoles and, for example, U.S. Pat. Nos. 3,004,896, 3,055,896, 3,072,585, 3,074,910, 3,189,615, 3,218,332, 3,230,194, 4,127,586, 4,226,763, 4,275,004, 4,278,589, 4,315,848, 4 347180, 4383863, 4675352, 4681905, 4853471, 5268450, 5278314, 5280124, 5319091, 5410071, 5436349, 5516914, 5554760, 5563242, 5574166, 5607987, 5977219 and 6166218 disclosed benzotriazoles.
[0154] Examples of UV absorbers include 2-(2-hydroxy-5-methylphenyl)-2H-benzotriazole, 2-(3,5-dibutyl-2-hydroxyphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)-2H-benzotriazole, 5-chloro-2-(3,5-di-tert-butyl-2-hydroxyphenyl)-2H-benzotriazole, 5-chloro-2-(3-tert-butyl-2-hydroxy-5-methylphenyl)-2H-benzotriazole, 2-(3-sec-butyl-5-tert-butyl-2-hydroxyphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)-2H-benzotriazole, 2-hydroxy-4-octyloxyphenyl)-2H-benzotriazole, 2-(3,5-di-tert-amyl-2-hydroxyphenyl)-2H-benzotriazole, 2-(3,5-bis-α-cumyl-2-hydroxyphenyl)-2H-benzotriazole, 2-(3-tert-butyl-2-hydroxy-5-(2-(ω-hydroxy-octyl-(vinyloxy)carbonyl-ethyl)-phenyl)-2H-benzotriazole, 2-(3-dodecyl-2-hydroxy-5-methylphenyl)-2H-benzotriazole, 2-(3-tert-butyl-2-hydroxy-5-(2-octyloxycarbonyl)ethylphenyl)-2H-benzotriazole, dodecyl 2-(2-hydroxy -5-methylphenyl)-2H-benzotriazole, 2-(3-tert-butyl-2-hydroxy-5-(2-octyloxycarbonyl-ethyl)phenyl)-5-chloro-2H-benzotriazole, 2-(3-tert-butyl-5-(2-(2-ethylhexyloxy)-carbonylethyl)-2-hydroxyphenyl)-5-chloro-2H-benzotriazole, 2-(3-tert-butyl-2-hydroxy-5-(2-methoxycarbonyl-ethyl)phenyl)-5-chloro-2H-benzotriazole, 2-(3-tert-butyl-2-hydroxy-5-(2-methoxycarbonyl-ethyl)phenyl)-2H-benzotriazole, 2-(3-tert-butyl-5-(2-(2-ethylhexyloxy)-carbonylethyl)-2-hydroxyphenyl)-5-chloro-2H-benzotriazole 2-(2-hydroxy-3-α-cumyl-5-tert-octylphenyl)-2H-benzotriazole, 2-(2-hydroxy-3-α-cumyl-5-tert-octylphenyl)-2H-benzotriazole, 2-(2-hydroxy-3-α-cumyl-5-tert-octylphenyl)-2H-benzotriazole, 2-(2-hydroxy-3-tert-octyl-5-α-cumylphenyl)-2H-benzotriazole, 5-fluoro-2-(2-hydroxy-3,5-di-α-cumylphenyl)-2H-benzotriazole, 5-chloro-2-(2-hydroxy-3,5-di-α-cumylphenyl)-2H-benzotriazole, 5-chloro-2-(2-hydroxy-3,5-di-α-cumylphenyl)-2H-benzotriazole, 5-chloro-2-(2-hydroxy-3-α-cumyl-5-tert-octylphenyl)-2H-benzotriazole, 2-(3-tert-butyl-2-hydroxy-5-(2-isooctyloxycarbonylethyl)phenyl)-5-chloro-2H-benzotriazole, 5-trifluoromethyl-2-(2-hydroxy-3-α-cumyl-5-tert-octylphenyl)-2H-benzotriazole, 5-trifluoromethyl-2-(2-hydroxy-5-tert-octylphenyl)-2H-benzotriazole, 5-trifluoromethyl-2-(2-hydroxy-3,5-di-tert-octylphenyl)-2H-benzotriazole, 3-(5-trifluoromethyl-2H-benzotriazol-2-yl)-5-tert-butyl -4-hydroxycinnamic acid methyl ester, 5-butylsulfonyl-2-(2-hydroxy-3-α-cumyl-5-tert-octylphenyl)-2H-benzotriazole, 5-trifluoromethyl-2-(2-hydroxy-3-α-cumyl-5-tert-butylphenyl)-2H-benzotriazole, 5-trifluoromethyl-2-(2-hydroxy-3,5-di-tert-butylphenyl)-2H-benzotriazole, 5-trifluoromethyl-2-(2-hydroxy-3,5-di-α-cumylphenyl)-2H-benzotriazole, 5-butylsulfonyl-2-(2-hydroxy-3,5-di-tert-butylphenyl)-2H-benzotriazole and 5-benzenesulfonyl-2-(2-hydroxy-3,5-di-tert-butylphenyl)-2H-benzotriazole. ,
[0155] The disadvantage is that some of these UV stabilizers are classified as hazardous substances according to the current EU regulations on classification, labeling and packaging of chemical substances. 2-(2H-benzotriazol-2-yl)-4-methylphenol is classified as a hazardous substance because it is persistently toxic to aquatic organisms and may cause allergic skin reactions. And, from an ecological and economic point of view, reducing the amount of UV stabilizers is advantageous.
[0156] In view of this, it is desirable to reduce the amount of conventional UV stabilizers such as 2-(2H-benzotriazol-2-yl)-4-methylphenol in polymer compositions. The inventors surprisingly found that conventional UV absorber compounds, such as UV absorber compounds containing benzotriazole groups, in particular UV absorber compounds of 2-(2H-benzotriazol-2-yl)-4-methylphenol, can be partially or completely replaced by the absorber component C used in the thermoplastic molding composition P according to the invention, which absorber component C comprises at least one dye having UV absorption at least in the wavelength range of ≤380 nm, at least one white pigment and / or at least one black pigment.
[0157] Therefore, according to the present invention, the UV absorber component C at least partially comprises at least one organic or inorganic component selected from at least one black pigment, a white pigment and / or at least one dye having UV absorption at least in the wavelength range of ≤380nm, preferably 100nm-380nm, more preferably 200nm-380nm, and especially 250nm-380nm. More preferably, the UV absorber component C at least partially comprises at least one dye having UV absorption at least in the wavelength range of ≤380nm, at least one white pigment and / or at least one black pigment. In another preferred embodiment, the UV absorber component C is at least partially composed of at least one dye having UV absorption at least in the wavelength range of ≤380nm and carbon black and / or at least one white pigment. In another preferred embodiment, the UV absorber component C at least partially comprises at least one dye having UV absorption at least in the wavelength range of ≤380nm selected from red, orange and yellow dyes, especially yellow dyes, having UV absorption at least in the wavelength range of ≤380nm. However, the composition may contain other dyes, colorants and / or pigments that do not meet these specifications to adjust the visual effect to meet user specifications.
[0158] Suitable pigments include carbon black and titanium dioxide.
[0159] Suitable dyes include, for example, Yellow K 1090 (BASF SE, CAS number: 30125-47-4), Yellow K 2011FG (BASF SE, CAS number: 68186-90-3), Yellow K 1160FG (BASF SE, CAS-No.: 14059-33-7).
[0160] The present inventors have found that conventional UV absorbers, especially compounds containing a benzotriazole group represented by the following formula (I) and mixtures thereof, can be partially or completely replaced by a UV absorber component C, wherein the UV absorber component C is at least one dye having UV absorption at least in a wavelength range of ≤380 nm, at least one white pigment and / or at least one black pigment:
[0161] Among them, R1, R2, R3, R4, R5, R6, R7, and R8 are respectively selected from a hydrogen atom, a halogen atom, and an alkyl group having 1 to 5 carbon atoms.
[0162] In particular, 2-(2H-benzotriazol-2-yl)-4-methylphenol (CAS No. 2440-22-4, commercially available from BASF SE, Germany) represented by formula (Ia) is P) can advantageously be replaced by the UV absorber component C according to the invention.
[0163] Other suitable UV absorbers that may be substituted according to the present invention include 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol ( 326), represented by the following formula (Ib):
[0164] In one embodiment of the present invention, the UV absorber component C comprises a compound of formula (I), (Ia) and / or (Ib). Preferably, the UV absorber component C comprises a compound of formula (Ia).
[0165] In one embodiment of the present invention, the compound containing benzotriazole groups is partially, more preferably completely, replaced by an organic or inorganic component UV absorber selected from at least one black pigment, white pigment and / or at least one dye having UV absorption in a wavelength range of ≤380 nm. In a more preferred embodiment, based on the thermoplastic molding composition P, the thermoplastic molding composition P contains ≤0.2% by weight of 2-(2H-benzotriazole-2-yl)-4-methylphenol ( P), 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol represented by formula (Ib) 326) and / or a compound containing a benzotriazole group represented by the general formula (I).
[0166] In one embodiment, the amount of the components of formula (Ia), (Ib) and / or (I) is ≤0.05% by weight, even more preferably ≤0.01% by weight, and typically ≤0.001% by weight, based on the total weight of the thermoplastic molding composition P.
[0167] The weight ratio of substitution is preferably in the range of 1:0.5-1:10, i.e., 1 part by weight of the benzotriazole UV absorber is replaced by 0.5-10 parts by weight of at least one black pigment, white pigment and / or at least one dye having UV absorption at least in the wavelength range ≤380 nm. More preferably, the weight ratio is in the range of 1:1-1:5, especially in the range of 1:1.2-1:4.
[0168] In one embodiment of the present invention, the UV absorber component C is preferably composed of at least one organic or inorganic component selected from at least one black pigment, white pigment and / or at least one dye having UV absorption at least in the wavelength range of ≤380 nm or a mixture of at least two of the above. In a preferred embodiment, the UV absorber component C comprises a mixture of at least one black pigment, a white pigment and at least one dye having UV absorption at least in the wavelength range of ≤380 nm. This means that preferably no UV absorber component C according to formula (I), (Ia) and / or (Ib) is present in the thermoplastic molding composition P. More preferably, no other UV absorber component C is present in the thermoplastic molding composition P.
[0169] In an alternative embodiment of the present invention, the compound containing benzotriazole groups is only partially replaced by an organic or inorganic component selected from at least one black pigment, a white pigment and / or at least one dye having UV absorption at least in the wavelength range of ≤380 nm, wherein the thermoplastic molding composition P comprises 0.05-0.2% by weight, preferably 0.07-0.15% by weight, based on the thermoplastic molding composition P, of 2-(2H-benzotriazol-2-yl)-4-methylphenol ( P), 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol represented by formula (Ib) 326) and / or a compound containing a benzotriazole group represented by the general formula (I).
[0170] The amount of black pigment is preferably at least 0.05% by weight, more preferably at least 0.1% by weight, based on the total weight of the thermoplastic molding composition P. Usually, the amount of black pigment does not exceed 2.5% by weight, usually does not exceed 2% by weight.
[0171] The amount of white pigment is preferably at least 0.5% by weight, more preferably at least 1.0% by weight, based on the total weight of the thermoplastic molding composition P. Usually, the amount of white pigment does not exceed 3% by weight, usually does not exceed 2.5% by weight.
[0172] The amount of dye having UV absorption at least in the wavelength range ≤ 380 nm is preferably at least 0.05% by weight, more preferably at least 0.1% by weight, based on the total weight of the thermoplastic molding composition P. Typically, the amount of dye does not exceed 3% by weight, usually not more than 2.7% by weight.
[0173] To effectively act as a UV absorber, in a mixture of a dye with a black pigment and / or a white pigment, the black pigment is preferably present in an amount of at least 0.1% by weight, the white pigment is preferably present in an amount of at least 0.5% by weight, and the amount of the dye having UV absorption at least in the wavelength range of ≤380 nm is preferably at least 0.5% by weight. Therefore, a mixture of a dye with a black pigment and / or a white pigment containing less than 0.1% by weight of a black pigment and / or less than 0.5% by weight of a white pigment, and less than 0.5% by weight of a dye having UV absorption at least in the wavelength range of ≤380 nm, based on the total weight of the thermoplastic molding composition P, does not fall within the scope of the present invention. For example, small amounts of white pigment and / or black pigment are often used to adjust the color appearance to meet user specifications.
[0174] From the viewpoint of UV stability, the UV absorber component C preferably comprises at least one dye having UV absorption at least in the wavelength range of ≤380 nm. Optionally, the UV absorber component C further comprises at least one black pigment and / or at least one white pigment.
[0175] Other additives (component D)
[0176] The thermoplastic molding composition P according to the invention comprises, as optional component D, 0 to 10% by weight, typically 0.1 to 8% by weight, based on the molding composition P, of at least one further additive, wherein the additive D is different from the component C contained in the thermoplastic molding composition P.
[0177] The one or more further additives D used in the present invention may be any additive that can be used in the molding composition P. Suitable additives D include all substances that are usually used for processing or finishing polymers. For example, the further additives D may be selected from light stabilizers, antioxidants, co-stabilizers, plasticizers, lubricants, mold release agents, anti-dripping agents, matting agents and fillers. These further additives may be mixed at any stage of the preparation process, but are preferably mixed at an early stage in order to benefit from the stabilizing effect (or other specific effect) of the added substance as early as possible.
[0178] The additive D can be added in the form of a masterbatch containing the additive D in a polymer matrix. In a preferred embodiment, the additive D is added in the form of a masterbatch, which comprises 10-70% by weight, preferably 20-60% by weight of the additive D or a mixture thereof, and 30-90% by weight, preferably 40-80% by weight of a vinyl aromatic olefin and acrylonitrile copolymer as a matrix polymer, based on the total amount of the masterbatch. Preferably, the matrix polymer is selected from poly(styrene-acrylonitrile) (SAN), poly(α-methylstyrene / acrylonitrile) (AMSAN) and / or poly(styrene-methyl methacrylate) (SMMA).
[0179] Examples of additives D include, for example, light stabilizers (especially hindered amine light stabilizers), antioxidants (especially phenolic antioxidants), antistatic agents, antioxidants, flame retardants, stabilizers for improving thermal stability, stabilizers for increasing light stability, stabilizers for enhancing hydrolysis resistance and chemical resistance, anti-thermal decomposition agents, and lubricants, especially for the preparation of molded bodies / articles.
[0180] Examples of suitable antistatic agents include amine derivatives such as N,N-bis(hydroxyalkyl)alkylamines or N,N-bis(hydroxyalkyl)alkyleneamines, polyethylene glycol esters, copolymers of ethylene oxide glycol and propylene oxide glycol (especially diblock or triblock copolymers of ethylene oxide blocks and propylene oxide blocks), glyceryl monostearate and glyceryl distearate, and mixtures thereof.
[0181] Examples of suitable flame retardants that may be used include halogen-containing or phosphorus-containing compounds, magnesium hydroxide, and other common compounds known to those skilled in the art, or mixtures thereof.
[0182] Examples of suitable light stabilizers other than component C include various substituted resorcinols, salicylates, benzophenones, vitamin E and compounds of similar structures, and butylated condensation products of p-cresol and dicyclopentadiene. Other suitable compounds include, for example, thiocarboxylates. C6-C6 thiopropionic acid may also be used. 20 Alkyl esters, especially stearates and laurates. It is also possible to use dilauryl thiodipropionic acid (dilauryl thiodipropionate), distearyl thiodipropionic acid (distearyl thiodipropionate) or mixtures thereof.
[0183] Suitable matting agents include not only inorganic substances such as talc, glass beads or metal carbonates (e.g. MgCO3, CaCO3), but also polymer particles, especially with a diameter D 50Spherical particles larger than 1 μm are based, for example, on methyl methacrylate, styrene compounds, acrylonitrile or mixtures thereof. In addition, polymers containing copolymerized acidic and / or basic monomers can also be used.
[0184] Examples of suitable anti-drip agents include polytetrafluoroethylene (Teflon) polymers and ultra-high molecular weight polystyrene (weight average molar mass Mw greater than 2,000,000).
[0185] Examples of fiber / powder fillers include carbon or glass fibers in the form of glass fiber fabrics, glass mats or filament glass rovings, chopped glass, glass beads, and wollastonite, with glass fibers being particularly preferred. When glass fibers are used, they may be treated with sizing agents and coupling agents to improve compatibility with the blending components. The incorporated glass fibers may be in the form of short glass fibers or in the form of continuous filaments (rovings).
[0186] Examples of suitable particulate fillers include amorphous silica, magnesium carbonate, quartz powder, mica, bentonite, talc, feldspar or in particular calcium silicates such as wollastonite and kaolin.
[0187] Suitable lubricants and mold release agents include stearic acid, stearyl alcohol, stearic acid esters, polyolefin waxes and / or generally higher fatty acids and their derivatives and corresponding fatty acid mixtures containing 1 to 45 carbon atoms. In another preferred embodiment, the composition comprises a 1 -CONH-R 2 An amide compound wherein R 1 and R 2 are independently selected from saturated or unsaturated aliphatic hydrocarbon groups having 1 to 30 carbon atoms, preferably 12 to 24 carbon atoms, and especially 16 to 20 carbon atoms. In another preferred embodiment of the present invention, the composition may also contain a saturated or unsaturated aliphatic hydrocarbon group having formula R 3 -CO-OR 4 A fatty acid ester compound, wherein R 3 and R 4 Each is independently selected from saturated or unsaturated aliphatic hydrocarbon groups having 1 to 45 carbon atoms, preferably 15 to 40 carbon atoms, and especially 25 to 35 carbon atoms. Also particularly suitable is vinyl bisstearamide.
[0188] In another preferred embodiment, the thermoplastic polymer composition P may contain organic, inorganic or mixed phosphates, in particular alkaline metal or alkaline earth metal phosphates, such as Ca3(PO4)2 and / or organic phosphates having an alkyl or aryl group containing 1 to 12 carbon atoms. These phosphates can usually be added in the form of a masterbatch, for example in combination with a polyolefin wax and / or an olefin / styrene copolymer.
[0189] The thermoplastic molding composition P may also contain dyes, pigments or colorants as optional component D, which are different from the UV absorber component C described in the present invention. Particularly suitable dyes, pigments or colorants do not exhibit UV absorption in the wavelength range of at least ≤380 nm, especially in the wavelength range of 250-380 nm. These dyes are usually used to adjust the visual effect of the molding composition P to meet customer specifications.
[0190] In one embodiment of the present invention, the thermoplastic molding composition P preferably contains 0.1-1% by weight, preferably 0.15-0.9% by weight, more preferably 0.2-0.8% by weight, typically 0.3-0.7% by weight, based on the molding composition P, of at least one hindered amine light stabilizer as component D.
[0191] The thermoplastic molding composition P may comprise at least one hindered amine light stabilizer as component D, preferably selected from compounds having the following formula (II), and mixtures of hindered amine light stabilizers as component D represented by formula (II):
[0192] Wherein, R1 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms;
[0193] R2 represents a hydrocarbon group having 5 to 30 carbon atoms, wherein the hydrocarbon group preferably contains at least one heteroatom selected from N and O; and
[0194] R3, R4, R5, R6, R7, R8, R9 and R10 each represent a hydrogen atom or an alkyl group having 1 to 5 carbon atoms.
[0195] Hindered amine light stabilizers (HALS) are well known in the art. Known representative hindered amine light stabilizers include, for example, bis(2,2,6,6-tetramethylpiperidinyl) sebacate, bis(1,2,2,6,6-pentamethylpiperidinyl) sebacate, n-butyl-3,5-di-tert-butyl-4-hydroxybenzylmalonate (1,2,2,6,6-pentamethylpiperidinyl), condensation product of 1-hydroxyethyl-2,2,6,6-tetramethyl-4-hydroxypiperidine and succinic acid, condensation product of N,N'-(2,2,6,6-tetramethylpiperidinyl)-hexanediamine and 4-tert-octylamino-2,6-dichloro-s-triazine, tris(2,2,6,6-tetramethylpiperidinyl)-nitrilotriacetate, tetramethylpiperidinyl)- ... tris(2,2,6,6-tetramethylpiperidinyl)-nitrilotriacetate, tetramethylpiperidinyl)-1-hydroxyethyl-2,2,6,6-tetramethyl-4-hydroxypiperidine and succinic acid, condensation product of tris(2,2,6,6-tetramethylpi (2,2,6,6-tetramethyl-4-piperidinyl) 1,2,3,4-butanetetracarboxylate, 1,1'(1,2-ethanediyl)-bis(3,3,5,5-tetramethylpiperazinone), bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 1-(2-hydroxy-2-methylpropoxy)-4-octa-decanoyloxy-2,2,6,6-tetramethylpiperidine.
[0196] In a preferred embodiment, at least one hindered amine light stabilizer as component D is selected from the following compounds of formula (II-a) and mixtures thereof:
[0197] wherein R1 represents -H or -CH3; and
[0198] N represents an integer of 1-8, preferably an integer of 3-5, and especially 4.
[0199] In a preferred embodiment, the two substituents R1 are the same. More preferably, the two substituents R1 represent methyl -CH3.
[0200] Particularly preferred representatives of the hindered amine light stabilizer component D according to formula (II-a) include bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (CAS No.: 52829-07-9) and bis(1,2,2,6,6-pentamethylpiperidinyl) sebacate (CAS No.: 41556-26-7). The most preferred hindered amine light stabilizer component D according to formula (II-a) is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, which is commercially available from BASF SE, Germany. 770.
[0201] In a preferred embodiment of the present invention, the weight ratio of the at least one hindered amine light stabilizer component D to the at least one UV absorber component C (weight ratio HALS-D:C) is 1:5-5:1, more preferably 1:2-2:1, and further preferably 1:1.2-1.2:1. In a particularly preferred embodiment of the present invention, the weight ratio of the at least one hindered amine light stabilizer component HALS-D to the at least one UV absorber component C (weight ratio HALS-D:C) is about 1:1.
[0202] In one embodiment of the invention, the thermoplastic molding composition P may comprise as component D 0.01-1%, preferably 0.03-0.9% by weight, more preferably 0.04-0.8% by weight, typically 0.05-0.7% by weight, based on the molding composition P, of at least one antioxidant.
[0203] The thermoplastic molding composition P may comprise, as component D, at least one antioxidant, preferably selected from the group consisting of sterically hindered phenolic antioxidants of the general formula (III) and mixtures thereof:
[0204] wherein R1 to R5 represent a hydrogen atom or an alkyl group having 1-70 carbon atoms, respectively, wherein the hydrocarbon group optionally contains at least one heteroatom selected from O and S, and at least one of the substituents R1 and R5 represents a hydrocarbon group having at least 3 carbon atoms.
[0205] Particularly preferred representatives of sterically hindered phenolic antioxidants as component D include octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (CAS No. 2082-79-3, commercially available from BASF SE, Germany). 1076), pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (CAS No. 6683-19-8, commercially available from BASF SE, Germany 1010), ethylenebis(oxyethylene)bis-(3-(5-tert-butyl-4-hydroxy-m-tolyl)-propionate) (CAS No.: 36443-68-2, commercially available from BASF SE, Germany 245), 4,4'-thiobis(2-tert-butyl-5-methylphenol) (CAS No. 96-69-5, commercially available from BASF SE, Germany BB12P and R), poly(dicyclopentadiene-co-p-cresol) (butylated reaction product of p-cresol and dicyclopentadiene, preferably having an average molecular weight of 650 g / mol, CAS No.: 68610-51-5, commercially available from Omnova Solutions L), pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (CAS No.: 2082-79-3), ethylenebis(oxyethylene)bis-(3-(5-tert-butyl-4-hydroxy-m-tolyl)-propionate) (CAS No. 36443-68-2). Particularly preferred are pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (CAS No.: 2082-79-3), ethylenebis(oxyethylene)bis-(3-(5-tert-butyl-4-hydroxy-m-tolyl)-propionate) (CAS No. 36443-68-2), 4,6-bis(dodecylthiomethyl)-o-cresol (CAS No. 36443-68-2), 4,6-bis(dodecylthiomethyl)-o-cresol (CAS No. 36443-68-2) and mixtures thereof.
[0206] The composition may also contain antioxidants different from the above-mentioned hindered phenolic antioxidants. Examples of suitable antioxidants include sterically hindered monocyclic or polycyclic phenolic antioxidants different from the above-mentioned component hindered phenolic antioxidants, which may contain various substitutions and may also be bridged by substituents. These include not only monomeric compounds, but also oligomeric compounds, which may be composed of multiple phenolic units. Hydroquinone and hydroquinone analogs are also suitable, as are substituted compounds, and antioxidants based on tocopherol and derivatives thereof are also suitable. Mixtures of different antioxidants may also be used. In principle, any compound conventional in the industry or suitable for styrene copolymers may be used.
[0207] In addition to the phenolic antioxidants mentioned above as examples, so-called co-stabilizers, in particular phosphorus- or sulfur-containing co-stabilizers, can also be used. These phosphorus- or sulfur-containing co-stabilizers are known to those skilled in the art and can be used alone or in combination with one another.
[0208] Preparation of the molding composition P
[0209] The method according to the invention may have any procedural steps suitable for carrying out the claimed method.
[0210] In a preferred embodiment, the step of mixing the components comprises at least the following steps:
[0211] (i) providing predetermined amounts of components A to C and optionally component D to an optionally heatable mixing device; and
[0212] (ii) Mixing components A to C and, if present, component D in an optionally heatable mixing apparatus at a temperature above the glass transition point of components A to C to obtain a molding composition P.
[0213] Optionally, step (ii) may be preceded by a step of preparing a homogeneous particulate material mixture of components A to D. However, also when supplied to the optional heatable mixing device without prior mixing, homogeneous mixing is generally achieved in the optional heatable mixing device.
[0214] Each of components A to D (in terms of solids) may be provided in the form of a particulate material of varying particle sizes and particle size distributions (eg pellets, granules and / or powders).
[0215] Components A to D may be provided to the mixing device in the desired amounts and weight ratios as described above, and optionally mixed prior to mixing step (ii) to obtain a homogeneous mixture of particulate materials. In a preferred embodiment, this may take 1 to 60 minutes, preferably 1 to 20 minutes, especially 2 to 10 minutes, depending on the amount of particulate material to be mixed.
[0216] The homogeneous mixture of particulate materials thus obtained is then transferred to an optionally heatable mixing device and mixed therein to produce a substantially liquid-melt polymer mixture.
[0217] "Substantially liquid molten" means that the polymer mixture and the main liquid molten (softened) part may also contain a certain proportion of solid components, such as unmelted fillers and reinforcing materials, such as glass fibers, metal flakes or other unmelted pigments, colorants, etc. "Liquid molten" means that the polymer mixture has at least low fluidity and has therefore at least softened to the extent of having plasticity.
[0218] The mixing apparatus used are those familiar to the person skilled in the art. Components A to C and, if included, D can be mixed, for example, by co-extrusion, kneading or rolling, the components being isolated from the aqueous dispersion or solution obtained in the polymerization process.
[0219] Examples of mixing apparatus for carrying out the process include discontinuously operating and heated internal kneading apparatuses with or without RAM, continuously operating kneaders, such as continuous internal kneaders, screw kneaders with axially oscillating screws, Banbury kneaders, and also extruders, as well as roll mills, mixing roll mills with heated rolls and calenders.
[0220] The mixing device preferably used is an extruder or a kneader. Especially suitable for melt extrusion are, for example, single-screw or twin-screw extruders. Preference is given to twin-screw extruders. In some cases, the mechanical energy introduced by the mixing device during the mixing process is sufficient to melt the mixture, which means that the mixing device does not have to be heated. Otherwise, the mixing device is usually heated.
[0221] The temperature is determined by the chemical and physical properties of components A to D and should be selected to produce a substantially liquid molten polymer mixture. On the other hand, the temperature should not be too high to prevent thermal damage to the polymer mixture. However, the mechanical energy introduced can also be high enough that the mixing device may even need to be cooled. The mixing device is usually operated at 150-400° C., preferably 170-300° C.
[0222] In a preferred embodiment, a heatable twin-screw extruder is used at a speed of 50-150 rpm, preferably 60-100 rpm. In a preferred embodiment, an extrusion temperature of 170-270° C., preferably 210-260° C., is used to obtain the molding composition P. The molding composition P can be used directly, for example, in a molding process, preferably an injection molding process, or can be processed into granules that can be subsequently subjected to a molding process. The molding process is preferably carried out at a temperature of 170-270° C., especially 210-260° C. to obtain a molded article.
[0223] The processing can be carried out using known thermoplastic processing techniques, and production can be carried out in particular by thermoforming, extrusion, injection molding, calendering, blow molding, compression molding, press sintering, deep drawing or sintering, preferably by injection molding.
[0224] use
[0225] The thermoplastic molding compositions P are used for the preparation of molded articles for many applications. In view of the improved weathering stability, exterior applications or applications exposed to UV radiation are particularly preferred. Advantageously, molded articles comprising the thermoplastic molding compositions P may include, for example, components or articles for electronic devices, daily commodities and automotive exterior and / or interior parts, in particular for the production of visible components or articles. Preferred applications are for automotive exterior parts such as front grilles or rearview mirrors.
[0226] The invention will be further illustrated by examples and patent claims. DETAILED DESCRIPTION
[0227] Example
[0228] Components
[0229] preparation
[0230] The above components were mixed in a twin-screw extruder (model ZSK-30, from Cooperion GmbH, Germany) at Tm=250°C according to the weight ratios shown in Table 1 and Table 2 to prepare thermoplastic molding compositions.
[0231] Various samples were prepared by injection molding (Tm: 250°C).
[0232] Thermoplastic molding compositions with different UV absorbers as component C were prepared. The compositions are shown in Table 1. Table 1 Examples 1 to 4; Examples 1 and 2 contain 2% by weight of carbon black as a component of polymer composition AB-1 Components [% by weight] Example 1 Example 2 Example 3 Example 4 AB-1 99 99.5 --- --- AB-2 --- --- 97.49 97.99 C-1 0.5 --- 0.5 --- C-2 --- --- 0.07 0.07 C-3 --- --- 0.92 0.92 C-4 --- --- 0.5 0.5 C-5 --- --- 0.02 0.02 D-1 0.5 0.5 0.5 0.5
[0233] A number of test specimens of the compositions according to Examples 1 to 4 were prepared (prepared according to ISO 294 at a melt temperature of 250° C. and a mold temperature of 60° C.) and subjected to Xenotest 1200 weathering according to ISO 4892 / 2—Method A—External.
[0234] After the weathering time shown in Table 2, the impact strength of the unnotched test specimens of Example 1 and Example 2 was measured according to the pendulum impact test of ISO 180 standard. Table 2 Impact strength α of Example 1 and Example 2 after artificial weathering n .
[0235] The surface gloss of the specimens was also evaluated. The initial and residual gloss after artificial weathering was determined according to DIN EN ISO 2813 at a measuring angle of 60°. The evaluation results are shown in Table 3. Table 3 Residual gloss (%) after artificial weathering of Examples 1 to 4. Weathering time h Example 1 Example 2 Example 3 Example 4 0 94 93 95 95 400 85 85 88 88 800 83 82 79 79 1200 83 83 78 78
[0236] In addition, the color migration dE of the test samples was evaluated. The initial chromaticity and the residual chromaticity after artificial weathering were determined according to the color measurement method of DIN 6174. The test results are summarized in Table 5. Table 5 Color migration dE of Examples 3 and 4 after artificial weathering. Weathering time h Example 3 Example 4 0 0 0 2000 4 4.5 4000 6 7 6000 7 10
[0237] Thermoplastic molding compositions with different UV absorbers as component C were prepared. The compositions are shown in Table 6. Table 6 Examples 5 and 6 Components [% by weight] Example 5 Example 6 AB-2 95.41 95.91 C-1 0.5 --- C-2 0.02 0.02 C-5 1.25 1.25 C-6 1.19 1.19 C-7 1.13 1.13 D-1 0.5 0.5
[0238] Test specimens of the compositions according to Example 5 and 6 were prepared (prepared in a mold family according to ISO 294 at a melt temperature of 250°C and a mold temperature of 60°C) and subjected to Xenotest 1200 weathering according to ISO 4892 / 2 - Method A - External.
[0239] The surface gloss of the test samples was evaluated. The initial and residual gloss after artificial weathering was determined according to DIN EN ISO 2813, with a measurement angle of 60°. The evaluation results are shown in Table 7. Table 7 Residual gloss (%) of Example 5 and Example 6 after artificial weathering. Weathering time h Example 5 Example 6 0 96 95 1000 85 83
[0240] In addition, the color migration dE of the test samples was evaluated. The initial chromaticity and the residual chromaticity after artificial weathering were determined according to the color measurement method of DIN 6174. The test results are summarized in Table 8. Table 8 Color migration dE of Example 5 and Example 6 after artificial weathering. Weathering time h Example 5 Example 6 0 0 0 2000 3 4 4000 4.5 5.5
[0241] The experimental data in Tables 1 to 8 show that the UV absorber 2-(2H-benzotriazol-2-yl)-4-methylphenol can be completely replaced by the dyes and / or pigments of the invention without substantial deterioration of the mechanical properties (impact strength) and optical properties (surface gloss and color shift dE) of the thermoplastic molding composition. Similar results were observed for the thermoplastic molding compositions of the invention comprising components A to D according to the invention.
Claims
1. A thermoplastic molding composition P, comprising: AB: 86-99.9% by weight, based on the molding composition P, of at least one graft copolymer component AB, comprising: A: Based on the composition AB, 30-80% by weight of at least one thermoplastic copolymer A, which is made from the following components: A1: Based on the copolymer A, 50-95% by weight of monomer A1 is selected from styrene, α-methylstyrene and styrene and at least one selected from α-methylstyrene, p-methylstyrene and C 1 -C 8 A mixture of other monomers of alkyl (meth) acrylate; A2: based on the copolymer A, 5-50% by weight of monomer A2, selected from acrylonitrile and a mixture of acrylonitrile and at least one other monomer selected from methacrylonitrile, acrylamide, vinyl methyl ether, unsaturated carboxylic acid anhydride and unsaturated carboxylic acid imide; B: Based on the composition AB, 20-70% by weight of at least one graft copolymer B, comprising: B1: Based on the graft copolymer B, 50-90% by weight of at least one graft base B1 is obtained by emulsion polymerization of the following components: B11: Based on the graft base B1, 70-99.9% by weight of at least one C 1 -C 8 Alkyl (meth)acrylate as monomer B11; B12: based on the graft base B1, 0.1-10% by weight of at least one multifunctional crosslinking monomer B12; B13: based on the graft base B1, 0-29.5% by weight, preferably 0-20% by weight, particularly preferably 0-10% by weight of at least one other copolymerizable monomer B13; in, The totality of B11+B12+B13 provides 100% by weight of the at least one graft base B1; and B2: Based on the graft copolymer B, 10-50% by weight of at least one graft shell B2, obtained by emulsion polymerization of the following components in the presence of at least one graft base B1: B21: Based on the graft shell B2, 50-100% by weight of a monomer B21 selected from styrene, α-methylstyrene and styrene and at least one selected from α-methylstyrene, p-methylstyrene and C 1 -C 4 A mixture of other monomers of alkyl (meth) acrylate; B22: 0-50% by weight of monomer B22, based on the graft shell B2, selected from acrylonitrile and a mixture of acrylonitrile and at least one other monomer selected from methacrylonitrile, acrylamide, vinyl methyl ether, unsaturated carboxylic acid anhydrides and unsaturated carboxylic acid imides; B23: 0-20% by weight of at least one other copolymerizable monomer B23; Wherein, B21+B22+B23 as a whole provide 100% by weight of the at least one graft shell B2; wherein the graft base B1 and the graft shell B2 as a whole provide 100% by weight of the at least one graft copolymer B; C: 0.1 to 4% by weight, based on the molding composition P, of at least one UV absorber as component C; and D: 0-10% by weight of at least one other additive as component D, based on the molding composition P; wherein the total amount of components A to D is 100% by weight of the molding composition P, and Wherein, the UV absorber component C comprises at least one organic or inorganic component having UV absorption at least in a wavelength range of ≤380 nm; and wherein the UV absorber component C is at least partially selected from at least one black pigment, at least one white pigment and / or at least one dye having UV absorption at least in a wavelength range of ≤380 nm, preferably 100 nm-380 nm, more preferably 200 nm-380 nm, and especially 250 nm-380 nm.
2. The thermoplastic molding composition P according to claim 1, It is characterized in that The weight average particle size dw of the graft copolymer component B is at least 50 nm, preferably at least 80 nm, more preferably at least 90 nm.
3. The thermoplastic molding composition P according to claim 1 or 2, It is characterized in that The UV absorber component C comprises at least one dye having UV absorption at least in the wavelength range of 250 nm to 380 nm, at least one white pigment and / or at least one black pigment.
4. The thermoplastic molding composition P according to any one of claims 1 to 3, It is characterized in that The UV absorber component C comprises at least one dye having UV absorption at least in a wavelength range of ≤380 nm and carbon black.
5. Thermoplastic molding composition P according to any one of claims 1 to 4, It is characterized in that The UV absorber component C comprises at least one dye selected from red, orange and yellow dyes having UV absorption at least in a wavelength range of ≤380 nm.
6. Thermoplastic molding composition P according to any one of claims 1 to 5, It is characterized in that The thermoplastic molding composition P comprises, as additive component D, at least one hindered amine light stabilizer.
7. The thermoplastic molding composition P according to claim 6, It is characterized in that The thermoplastic molding composition P comprises at least one hindered amine light stabilizer as component D, selected from a compound having the following formula (II) and a mixture of hindered amine light stabilizer components D represented by formula (II): Wherein, R1 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; R2 represents a hydrocarbon group having 5 to 30 carbon atoms, wherein the hydrocarbon group preferably contains at least one heteroatom selected from N and O; and R3, R4, R5, R6, R7, R8, R9, R10 each represent a hydrogen atom or an alkyl group having 1 to 5 carbon atoms.
8. Thermoplastic molding composition P according to claim 6 or 7, It is characterized in that The thermoplastic molding composition P comprises, as component D, at least one hindered amine light stabilizer selected from compounds of the following formula (II-a) and mixtures thereof: Wherein, R1 represents -H or -CH 3 ; and N represents an integer from 1 to 8.
9. Thermoplastic molding composition P according to any one of claims 1 to 8, It is characterized in that The UV absorber component C is selected from compounds containing a benzotriazole group represented by the following formula (I): Among them, R1, R2, R3, R4, R5, R6, R7, and R8 are respectively selected from a hydrogen atom, a halogen atom, and an alkyl group having 1 to 5 carbon atoms.
10. Thermoplastic molding composition P according to any one of claims 1 to 9, It is characterized in that The UV absorber component C represented by formula (I) is contained in an amount of less than 0.1% by weight based on the thermoplastic molding composition.
11. Thermoplastic molding composition P according to any one of claims 1 to 10, It is characterized in that The thermoplastic molding composition P comprises, as component D, 0.01 to 1% by weight, based on the molding composition P, of at least one antioxidant selected from the group consisting of sterically hindered phenolic antioxidants of the general formula (III) and mixtures thereof: wherein R1 to R5 represent a hydrogen atom or an alkyl group having 1-70 carbon atoms respectively, wherein the hydrocarbon group optionally contains at least one heteroatom selected from O and S, and at least one of the substituents R1 and R5 represents a hydrocarbon group having at least 3 carbon atoms.
12. Thermoplastic molding composition P according to any one of claims 1 to 11, It is characterized in that The thermoplastic molding composition P comprises, as component D, at least one phosphorus- or sulfur-containing costabilizer.
13. Thermoplastic molding composition P according to any one of claims 1 to 12, It is characterized in that The at least one graft copolymer composition AB comprises: A: based on the graft copolymer composition AB, 30-80% by weight of at least one thermoplastic copolymer as component A, selected from poly(styrene-acrylonitrile) (SAN), poly(α-methylstyrene / acrylonitrile) (AMSAN) and mixtures thereof; and B: Based on the graft copolymer composition AB, 20-70% by weight of at least one graft copolymer B, comprising: B1: Based on the graft copolymer B, 50-90% by weight of at least one graft base B1, obtained by emulsion polymerization of the following components: B11: based on the graft base B1, 70-99.9% by weight of n-butyl acrylate as monomer B11; B12: based on the graft base B1, 0.1-10% by weight of at least one multifunctional crosslinking monomer B12 selected from (meth)acrylate and / or dicyclopentadienyl acrylate (DCPA); wherein the total amount of B11 and B12 is equal to 100% by weight of B1; and B2: Based on the graft copolymer B, 10-50% by weight of at least one graft shell B2 is obtained by emulsion polymerization of the following components in the presence of at least one graft base B1: B21: 50-95% by weight of styrene monomer B21, based on the graft shell B2; and B22: 5-50% by weight of a monomer B22, based on the graft shell B2, selected from acrylonitrile or a mixture of acrylonitrile and at least one other monomer selected from methacrylonitrile; The total amount of the graft base B1 and the graft shell B2 is equal to 100% by weight of the graft copolymer B, and the weight average particle size dw of the at least one graft copolymer B is 50-1000 nm.
14. Use of the thermoplastic molding composition P according to any one of claims 1 to 13 for producing molded articles.
15. Moulded article comprising the thermoplastic moulding composition P according to any one of claims 1 to 13.
Citation Information
Patent Citations
Acrylic rubber graft copolymers combining high impact strength with good optical properties are obtained by starting with a seed polymer of particle size 10-50 nm
DE10308506A1
Stabilizer mixture containing three specific sterically hindered amine compounds, composition containing the stabilizer mixture and method for stabilizing organic material against degradation caused by light, heat or oxidation
DE10316198A1
impact-resistant thermoplastic molding compounds
DE1260135B
Graft polymer molding compounds with reduced deposit formation
DE19713509A1
molding compounds
DE2420358A1
